2011
DOI: 10.1159/000329635
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Physician-Supervised Self-Managed C1 Inhibitor Replacement Therapy

Abstract: Background: C1 inhibitor (C1INH) has recently been approved in the USA for the treatment of acute attacks in hereditary angioedema (HAE) patients. The literature suggests that treatment with C1INH is most effective when administered early in an attack. Home infusion of C1INH allows for the earliest possible intervention since patients can initiate therapy at the first sign of symptoms. Methods: We performed an observational, prospective study on 39 subjects with HAE utilizing two groups of patients: one receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…The study not only concluded that patients are capable of recognizing an attack and treating it appropriately, but also demonstrated, using patient satisfaction data, that the majority of patients preferred self-administering icatibant to receiving it from an HCP [21] . Not only is self-administration of icatibant beneficial to patients in terms of reduced attack duration and improved quality of life [15,22] , it may also confer substantial economic benefits, both in terms of direct health care costs and indirect savings, as has been demonstrated in a Spanish study [23] . The distribution of attack location and severity of HAE attacks treated with icatibant were similar between HCPand self-administered injections, suggesting that there were no disease-related barriers to self-treatment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study not only concluded that patients are capable of recognizing an attack and treating it appropriately, but also demonstrated, using patient satisfaction data, that the majority of patients preferred self-administering icatibant to receiving it from an HCP [21] . Not only is self-administration of icatibant beneficial to patients in terms of reduced attack duration and improved quality of life [15,22] , it may also confer substantial economic benefits, both in terms of direct health care costs and indirect savings, as has been demonstrated in a Spanish study [23] . The distribution of attack location and severity of HAE attacks treated with icatibant were similar between HCPand self-administered injections, suggesting that there were no disease-related barriers to self-treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Whatever the reasons, this finding demonstrates that a shift in approach to the management of acute attacks of HAE has occurred in recent years. Early treatment will directly reduce the total attack duration, and it has been suggested that early treatment may result in quicker symptom resolution and a reduced quality-of-life burden for patients [3,13,15,20,22,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although this trend is encouraging, it should be noted that only approximately onethird of respondents in 2013 reported that their patients with HAE were being treated most frequently at home, either through self-administration or with the assistance of home health care, despite unanimous recommendations for home-based care for all patients with HAE whenever feasible [18][19][20][21][22][23] and a growing body of published evidence that supports its feasibility and benefits. [26][27][28][29][30][31] Our survey found a surprisingly high percentage of physicians who still reported treatment of HAE attacks in the ED (53.9%), although hospital admission for treatment was reported significantly less in 2013 (2.6%). For C1-INH specifically, approximately two-thirds of use was characterized as administered in the home setting.…”
Section: Discussionmentioning
confidence: 75%
“…3,14 Evidence for Home Therapy in Pediatric HAE Home therapy in HAE has been demonstrated to be effective and well tolerated in adults, allowing early treatment of attacks and improved quality of life. [5][6][7][8] The feasibility of this approach in pediatric patients is less well established. There is a single retrospective observational study examining the efficacy and safety of home therapy in 20 pediatric HAE patients.…”
Section: Rationale For Home Therapy For Pediatric Haementioning
confidence: 99%